HISTORY OF SHALAHUDDIN AL-AYYUBI'S LEADERSHIP - Oktoberia, Selva Susila; Norhanah, Norhanah; Dakir, Dakir; Syahid, Abdul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Absrack Saladin Al-Ayyubi is one of the important figures in Islamic history who is known as the unifier of the people and the liberator of Jerusalem from the Crusaders. This article aims to analyze Saladin's leadership in strategic, military, and diplomatic aspects, as well as his contribution to building the unity of the Muslim community. This study uses a descriptive qualitative method based on literature review. The results of the analysis show that Saladin's success in capturing Jerusalem in 1187 was not only rooted in brilliant military strategy but also in effective management and a wise approach to his followers and enemies. His just and charismatic leadership is an example to this day, making him a symbol of an ideal leader in the history of Islamic civilization.